Anglo-French relations in the twentieth century : rivalry and cooperation - Sharp, Alan, 1943-; Stone, Glyn (Routledge, 2002)
Anglo-French Relations in the Twentieth Century is a collection of studies on the key episodes of the difficult and often discordant Anglo-French exchange over the past century. The authors critically re-evaluate: * the role of Spain in Anglo-French relations up to 1918 * the missed opportunity of the 1920s with the failure of France and Britain to find sufficient common ground and co-operation * the short-lived Anglo-French alliance and the Second World War * the degree of Anglo-French Imperial co-operation * the Suez Crisis * British and French policies on Europ.